Capacitación lingüística de ingreso en la UPNA Un estudio comparativo de varias titulaciones de grado - Bueno Alastuey, Mª Camino; Ballarín Castán, Ana (Huarte de San Juan. Filología y Didáctica de la Lengua, 2011)
The process of accreditation of levels of competence in foreign languages is such a heterogeneous process that a reflection has been recommended in the university context to define not only levels but also the way to achieve them. This study aims to be part of that reflection by analyzing the entry-level competence of students from five new degrees at the UPNA. The students took a computer level test. The grades in the entry-level test were used to explore both the adequacy of the required exit level of the different degrees and the differences depending on the exit level requirements of the degree, on gender and on the knowledge of other languages. The students’ level was also compared to their results in other level or entry assessments. Results indicated level A2 is the most common; that neither required exit level, nor gender, nor knowledge of other languages influenced the level obtained in the test; and that coincidences between test level and other tests level was high for levels A1, A2 and B1, but very low for higher levels, B2 and C1.